Perilaku Eksekutif dalam Menentukan Return Ekspektasian Melalui Program Opsi Saham - Ida Bagus Putra Astika (The Indonesian Journal of Accounting Research, 2013)
Previous research documents that executives manage earnings before the grant date and before the exercise of employee stock options (Yermark, 1997; Asyik, 2005). This study extends prior research by investigating whether the number of stock options granted is associated with earnings management before the grant date and whether the number of employee stok option exercised is associated with earnings management before the exercise date. I collect data from listed firms in Jakarta Stock Exchange that granted executive stock options from 1999 to 2005. Consistent with previous study, the results show the number of employee stock options granted is positively related to discretionary accruals before the grant date, suggesting that the more options a firm grants, the more likely executive manage earnings downward to lower the option exercise price. In addition, the study also shows that consistent with the hypothesis, the number of employee stok options exercised is positively related to discretionary accruals before the exercise date, indicating that the more options executives exercise the more likely they manage earnings upward before the exercise date to take advantage of a higher stock price